Pengaruh Panjang Sambungan Pada Beton Prategang Segmental Bertulangan Limbah Ban - Agus Maryoto (Jurnal Teknik Sipil dan Perencanaan)
Prestressed concrete with reinforcement of waste tires can improve significantly the flexural strength. The problems when applied in the project is difficult to move from the production site to the location of the structure. One method to overcome this is applied precast segmental. Molded concrete blocks with a shorter length is easy to carry to the project site. Connectors between concrete beams segment plays a very important thing. This study tried to determine the influence of length of connectors on the precast segmental concrete. Three specimens are concrete beam with no connections, segmental concrete blocks with a connection length of 10 cm and 15 used in the experiment. Flexural testing was conducted to determine the carrying capacity of the three beams. The result showed that the length of the connection contribute on flexural strength of concrete beam. However, segmental concrete beam flexural capacity was still below the concrete beam flexural capacity without connection.